DISEMINASI TEKNOLOGI ASAM HUMAT PADA BUDIDAYA PADI SAWAH DI KECAMATAN PALIMANAN KABUPATEN CIREBON - Diana Apriliya; Oeng Anwarudin; Nazaruddin Nazaruddin (Sekolah Tinggi Pariwisata Mataram, 2020)
DISEMINASI TEKNOLOGI ASAM HUMAT PADA BUDIDAYA PADI SAWAH DI KECAMATAN PALIMANAN KABUPATEN CIREBON Strategic steps to increase rice production in the government continue to be increased to meet domestic needs through the dissemination of technological innovation. One solution is the introduction of humic acid technology to streamline and improve the soil considering that the Palimanan District has the potential for lowland rice that can be developed. This study aims to analyze the description of technology dissemination and behavior of farmers, analyze the factors that influence the technology dissemination and behavior of farmers in use of humic acid in rice cultivation, and develop strategies to improve the process of technology dissemination to improve the behavior of farmers in the use of humic acid. This research was conducted in the village of Cilukrak, Palimanan sub-district, Cirebon regency, from April to June 2020. The research sample was 48 farmers determined through the Random Sampling Cluster technique. The variables of this study consisted of internal factors, external factors, the dissemination process, and farmer's behavior. Data collection is done through primary and secondary data. Data were processed using descriptive statistical analysis techniques and multiple regression and Kendall's W. The results showed that the process of dissemination of humic acid technology 72.9% included in the high category and the behavior of farmers 70.2% included in the medium category. Factors that significantly affect farmer's behavior are farmer education, land area, and dissemination process. Strategies to increase dissemination of humic acid and farmer's behavior can be done through increasing the intensity of farmer groups' meetings and functions.